Pro Windows Phone 7 development - Cameron, Rob (Apress ; Distributed to the Book trade worldwide by Springer Science+Business Media, 2011)
Presents information on creating Windows Phone 7 applications with Silverlight, .NET, XNA Framework, Visual Studio, and Expression Blend.